Two Physical Levels of Fundamental Particles That Determine Essence and Natural Independence of Electricity and Magnetism - Sizov, Robert A. (European Journal of Applied Sciences, 2022)
The experiments of F. Ehrenhaft, as well as the experimental and theoretical studies of the author, showed that it is the magnetic elementary particles (magnetic charges) that are the direct sources of the magnetic field and all magnetic manifestations in Nature. Eddy currents of magnetic charges (the rotating magnetic dipoles), which actually exist in the structures of a substance and are untwisted by means of an electric current in conductors, are direct sources of the well-known eddy magnetic field rotH. Together with electric charges, magnetic charges make up the shells of atoms, which are actually electromagnetic not electronic. It is the electromagnetic shells of atoms that are the sources of the vortex electromagnetic (gravitational) field, which is described by the vortex vector rot[E – H]. The main reason for ignoring magnetic charges, as well as true anti-electrons in physical science, is the harsh conditions for their retention in atoms and matter, which are fundamentally different from the retention of electrons. The introduction of magnetic charges into basic physics showed that the real Physical World is formed by three global phases: Matter, Antimatter and Energo-medium which make up the world Physical Triad. Each of the noted phases is formed by its own fundamental particles. The material phase or Matter is formed by spinor (charged) particles of electrical and magnetic nature with a negative charge. The antimaterial phase or Antimatter is formed by magnetic and electric particles with a positive charge. The third phase of the Physical Triad is a super-dense Energo- medium (Energo-ether), which fills the entire space of the real World and consists of its own ultra-small elementary particles, which received the author’s name - energions. Energions are massless and spinless particles moving in all directions at near-light speeds. The author showed that particles-energions in the composition of the Energo-medium are divided into two natural groups: Electro-energions and Magneto-energions. In addition, the energions in each of the marked groups differ in the direction of their own rotation which can be either left or right. Thus, the particles of the Energo-medium are doubly degenerate which, together with the discovered magnetic charges and true anti-electrons, determines the physical essence of electricity and magnetism, as well as their natural independence. The vector character of the gravitational field is in many respects similar to the vortex magnetic field, which has been known for hundreds of years, but no one has come up with the version of spatial magnetic waves. Therefore, the version of gravitational waves, according to the author, is another fake, inspired by crooked physics, in which real magnetic charges are ignored and, as a result, there is no representation of the real physics of the gravitational field.